2014
DOI: 10.1002/dev.21264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal fluoxetine exposure on behavior across development in rats selectively bred for an infantile affective trait

Abstract: Infants born to women with depressive symptoms are at higher risk for insecure attachment and behavioral problems. Thus current medical practice is to continue psychotropic medication of pregnant women with depression despite concerns about its behavioral teratology. There are few animal studies focused on long-term behavioral effects of prenatal antidepressant exposure; in addition, studies have not looked at individual differences in baseline affective state as a source of response variability. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Animal models converge with evidence from human studies as early exposure to SSRIs results in delayed motor abilities in pre-weaning offspring and juvenile offspring [131][132][133].…”
Section: Motor Developmentmentioning
confidence: 93%
“…Animal models converge with evidence from human studies as early exposure to SSRIs results in delayed motor abilities in pre-weaning offspring and juvenile offspring [131][132][133].…”
Section: Motor Developmentmentioning
confidence: 93%
“…At such concentrations, a mixture of fluoxetine, carbamazepine and venlafaxine, or valproate produce expression changes in genes related to neuronal growth, development and regulation, and to autism in SK-N-SH neuroblastoma cells [122]. Neonatal fluoxetine administration in rats impairs motor coordination in neonates and decreased social behaviour in both juvenile and adult offspring [123] Terbutaline ÎČ2-adrenergic receptor agonist, used as a tocolytic (anticontraction medication) to delay preterm labour for up to 48 hours Terbutaline exposure for >2 days during the third trimester associated with a fourfold increased risk for autism spectrum disorders (not observed with albuterol) [124] In rats, maternal stress during pregnancy, or terbutaline administration to the neonates, on postnatal days 2-5 resulted in autistic-like behaviour in the offspring (stereotyped/repetitive behaviour and deficits in social interaction or communication [125]. Newborn rats treated with terbutaline (10 mg/kg) daily on postnatal days 2 to 5 or PN 11 to 14 showed a robust increase in microglial activation on postnatal day 30 in the cerebral cortex, as well and in cerebellar and cerebrocortical white matter.…”
Section: Polychlorinated Biphenyls (Pcb)mentioning
confidence: 99%
“…Some studies have indicated that developmental SSRI exposure decreases social interaction in either male offspring [25,27] or female offspring [31], while others found an increase in sniffing behavior towards conspecifics [32,33]. When looking at the motivation for social interaction in particular, the majority found that SSRI exposure negatively affects the motivation to start social contact [26,28,29,34]. The inconsistent results make it impossible to draw conclusions about the risk for long-term affected social behavior in the offspring.…”
Section: Introductionmentioning
confidence: 99%